2016
DOI: 10.1177/1097184x16652656
|View full text |Cite
|
Sign up to set email alerts
|

Speaking of Stigma and the Silence of Shame

Abstract: This study addresses male sexual victimization as that which is both invisible and incomprehensible. Forensic interviews with young men following reports of suspected sexual assault reveal patterns of heteronormative scripts appropriated to make sense of sexual victimization. These scripts show that victimhood is largely incompatible with dominant notions of masculinity. Sexual coercion and assault embodied threat to boys' (hetero)gendered selves, as they described feelings of shame and embarrassment, disempow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 62 publications
4
77
2
2
Order By: Relevance
“…When they perceive that others will consider the encounter as trivial or as the young person's fault, children and young people are less likely to share the experience with others or seek support (Schönbucher, Maier, Mohler-Kuo, Schnyder, & Landolt, 2012). Fear of negative reactions from others, including doubt, disbelief or indifference (Hlavka, 2016), are also powerful disincentives, as are fears of stigmatisation, breaches of confidentiality and fears of being seen as 'attention-seeking' (Rowe et al, 2014). Studies have also shown that children and young people are less likely to disclose to adults and institutions they perceive are incompetent, and when they have little faith that the adults or institutions can adequately respond or protect them (Ungar et al, 2009).…”
Section: The Value Of Gauging Children's Perceptionsmentioning
confidence: 99%
“…When they perceive that others will consider the encounter as trivial or as the young person's fault, children and young people are less likely to share the experience with others or seek support (Schönbucher, Maier, Mohler-Kuo, Schnyder, & Landolt, 2012). Fear of negative reactions from others, including doubt, disbelief or indifference (Hlavka, 2016), are also powerful disincentives, as are fears of stigmatisation, breaches of confidentiality and fears of being seen as 'attention-seeking' (Rowe et al, 2014). Studies have also shown that children and young people are less likely to disclose to adults and institutions they perceive are incompetent, and when they have little faith that the adults or institutions can adequately respond or protect them (Ungar et al, 2009).…”
Section: The Value Of Gauging Children's Perceptionsmentioning
confidence: 99%
“…But the items we have included all address the experience of being penetrated, while the penal code also covers incidents of forcing someone to penetrate someone else, including the assailant. 1 In the literature, this type of sexual assault is labelled 'made to penetrate', 'forced to penetrate' and 'compelled penetration' (Hlavka, 2017;Stemple & Meyer, 2014;Weiss, 2010). None of the Norwegian prevalence studies have included questions about 'forced-to-penetrate' rapes, so the prevalence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that gendered and heteronormative discourses structure how individuals understand their social worlds, including the experience of sexual violence (Hlavka, 2014(Hlavka, , 2017Nelson & Oliver, 1998;Phillips, 2000). My work on young women's descriptions of sexual assault and harassment demonstrates how heterogendered and heteronormative scripts are appropriated to account for violence.…”
Section: The Possibility Of Child Sexual Violencementioning
confidence: 99%
“…Rather than review the research on children and sexual violence, I argue that it is both possible and critical to open spaces for young people to speak about their experiences of sexual violence, thereby shifting from research on children and that speaks for children, toward research with children. I also join the growing chorus of sociologists and anthropologists who have recently drawn attention to the disciplinary silences on sexual violence (Armstrong, Gleckman-Krut, & Johnson, 2018;Baxi, 2014) and specifically to the omission of children and youth (e.g., Hlavka, 2010Hlavka, , 2014Hlavka, , 2017Korbin, 2003;A. J. Powell, Hlavka, & Mulla, 2017;Shanahan, 2007;Whittier, 2016).…”
mentioning
confidence: 99%